The Elimination of the Judge's Mandate and Its Effect on the Civil Judiciary - Ameen Al-Jaf, Fwrat Rostam (2020)
The function of the judiciary is to protect the law system and the law rights and centers by a request applied to it by the concerned persons, and by issuing decisions and verdicts that remove the state of ignoring which surrounds the right or the law center wanted to be protected in which it gets the binding force of the thing judged owing to its issue which prevents the review of the dispute among the same fellows for the same subject and cause. For the judicial verdict to get the binding force of the thing sentences, it must be issued by a judge in limits of his judicial sponsorship, also, it must be issued in the legally decided form. So, If the judicial sponsorship removed from the judge, for any reason, there will be important results that we will deal with them in this study. And since the Iraqi Law of civil pleadings did not address this issue, we will try in this study to find the best legal ways to address the above topic.